ผลของการออกกำลังกายเป็นประจำ และการบริโภคอาหารต่อระดับการต้านอนุมูลอิสระ และความเสี่ยงต่อโรคหัวใจและหลอดเลือดในผู้สูงอายุ : รายงานผลการวิจัย - อรรถกร ปาละสุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The decline metabolic function in elderly increases risk of oxidative stress, leading to cardiovascular diseases. Adequate physical activity and well-balance diet would help to reduce the risks. This study aimed to compare antioxidant status and risk of cardiovascular diseases associate with dietary intake and regular exercise effects. A cross-sectional study was conducted in sedentary elderly (SE, n=17), exercising elderly (EE, n=26) who had exercise activity at least 3 hours/week for a year, sedentary young (SY, n=37) and exercising young (EY, n=12). All participants completed 4-day dietary intake records. Blood was collected on day 5. Factorial ANOVA tests were done regarding to aging and exercising factors. We found that total antioxidant status (TAS) and homocysteine (tHcy) in plasma were significantly and independently depended on elderly and exercise status. Elderly group had higher TAS and tHcy, compared to young group (p<0.01). EE had higher TAS compared to SE, EY and SY (p<0.001), and higher erythrocyte glutathione peroxidase activity compared to SY และ EY (p<0.05). SE had higher tHcy compared to EE, EY and SY (p<0.01). We evidenced that TAS was related to body mass index (r=0.337, p=0.002), % body fat mass (r=0.402, p=<0.0001), vitamin C intake (r=0.231, p=0.026), while tHcy was related to the decrease of plasma HDL concentration (r=-0.269, p=0.015). No differences were shown on lipid peroxidation marker (TBARS), plasma ascobate, erythrocyte superoxide dismutase activity. We suggest that regular exercise would help to increase antioxidant protection status and decrease the risk of cardiovascular diseases in elderly.